2018
DOI: 10.30880/jst.2018.10.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Environmental Conditions to Phytoconstituents in Clitoria ternatea (Butterfly Pea Flower) – A Review

Abstract: Extreme environmental conditions will consequently become a disturbance on all phases of plant growth. Malaysia is one of the developing countries that face challenges of extreme environmental conditions from climate change such as water availability and soil salinity. In response to global climate change, plants are trying to survive through several adaptation mechanisms. Clitoria ternatea or also known as Butterfly pea flower is a potential plant that can tolerate different environmental parameters. Besides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 65 publications
0
20
0
3
Order By: Relevance
“…Further, anthocyanin prevents diabetes, protects the cardiovascular system from damage, and many more health benefits (13) . Moreover, research findings suggested that anthocyanin helps in protecting the cell as an anti-aging agent, protects cell damage, and promoting healthy eyes (14) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, anthocyanin prevents diabetes, protects the cardiovascular system from damage, and many more health benefits (13) . Moreover, research findings suggested that anthocyanin helps in protecting the cell as an anti-aging agent, protects cell damage, and promoting healthy eyes (14) .…”
Section: Introductionmentioning
confidence: 99%
“…Natural dye from C. ternatea could be a coloring agent for making products (14) . In countries like China and Malaysia, people used C. ternatea flowers for making blue colored tea and blue rice.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, CT flower extract was used as the stabilizing agent in producing Ag NPs. It contains high amount of anthocyanin pigments compare to other flowers which is the main components in the green synthesis process [15].…”
Section: Introductionmentioning
confidence: 99%
“…C. ternatea flowers contain phenolic compounds, flavonoids, anthocyanins, saponins, alkaloids, and anthocyanidins (Kaisoon et al, 2011;Nair et al, 2015). The bioactive compounds of these flowers are however very sensitive to various changes in the environment (Pa'ee et al, 2018). In order to retain bioactive compounds, encapsulation technologies are introduced to provide maximum protection for encapsulated bioactive compounds (Talegaonkar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%